The Effect of Hepatic Impairment on the Pharmacokinetics of Asunaprevir, an HCV NS3 Protease Inhibitor. Issue 1 (January 2015) - Eley, Timothy; He, Bing; Chang, Ih; Colston, Elizabeth; Child, Michael; Bedford, William; Kandoussi, Hamza; Pasquinelli, Claudio; Marbury, Thomas C; Bertz, Richard J
Background: It is necessary to evaluate the impact of hepatic impairment on the pharmacokinetic profile of direct-acting antiviral agents for the treatment of HCV infection. Methods: In this open-label, parallel group, multiple-dose study subjects (aged 18–70 years with a body mass index <35 kg/m 2 ) with mild ( n =6), moderate ( n =6) and severe hepatic impairment ( n =4) received asunaprevir 200 mg twice daily; healthy subjects ( n =12) were matched (age, weight, gender) 1:1 to the first 4 subjects in each hepatic impairment group to act as controls. Pharmacokinetic sampling and analyses were performed on days 1 and 7 of dosing. Pharmacokinetic parameters were derived by non-compartmental methods. Geometric mean ratios (GMRs) and 90% CIs were used to assess the impact of hepatic impairment on the pharmacokinetics of asunaprevir, relative to healthy matched controls. Results: Compared with healthy subjects, mild hepatic impairment did not result in meaningful alterations in asunaprevir exposure (day 7 maximal plasma concentration [Cmax ] GMR: 0.58 [90% CI 0.35, 0.98]; area under the plasma concentration–time curve in one dosing interval [AUCtau ] GMR: 0.79 [90% CI 0.55, 1.15]); clinically significant increases in asunaprevir exposure were observed in subjects with moderate (Cmax GMR: 5.03 [90% CI 2.99, 8.47]; AUCtau GMR: 9.83 [90% CI 6.76, 14.28]) and severe hepatic impairment (Cmax GMR: 22.92 [90% CI 12.57, 41.81]; AUCtau GMR: 32.08 [90% CI 20.84, 49.40]). Correlation between increased asunaprevir exposure and all individual components of the Child–Pugh classification system was observed in subjects with moderate and severe hepatic impairment. Conclusions: Mild hepatic impairment does not meaningfully affect the pharmacokinetic profile of asunaprevir. The dosing of asunaprevir in patients with moderate-to-severe hepatic impairment is not recommended. Clinicaltrials.gov identifier NCT01019070.